Finite state automaton based control system for walking machines. (30th May 2019) - Hussain, Razeen; Zielinska, Teresa; Hexel, Rene
Walking machines have proved to be an important invention as they do not require any prepared surface, making them ideal for applications involving unexplored environments. They are equipped with a large number of actuators and sensors to achieve a robust locomotion; thus, a systematic approach to designing their control system is required. This article presents a functional control structure based on the logic-labelled finite state automaton approach developed for walking machines. A general control structure is presented and a hexapod robot is used to verify the practicability of the design.